2016
DOI: 10.1145/2893186
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Computer Architectures and Software Systems for Phase-Change Memory

Abstract: With dramatic growth of data and rapid enhancement of computing powers, data accesses become the bottleneck restricting overall performance of a computer system. Emerging phase-change memory (PCM) is byte-addressable like DRAM, persistent like hard disks and Flash SSD, and about four orders of magnitude faster than hard disks or Flash SSDs for typical file system I/Os. The maturity of PCM from research to production provides a new opportunity for improving the I/O performance of a system. However, PCM also has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…A couple of related studies [94], [133] may further complement the results shown in this paper. We have identified that these studies share some of our motivations and objectives, although they present different approaches and obtain different results.…”
Section: Related Worksupporting
confidence: 77%
See 2 more Smart Citations
“…A couple of related studies [94], [133] may further complement the results shown in this paper. We have identified that these studies share some of our motivations and objectives, although they present different approaches and obtain different results.…”
Section: Related Worksupporting
confidence: 77%
“…Another study [133] explores the challenges of adopting Phase-Change RAM (PCM) as storage, main memory and/or processor cache, summarizing existing solutions and classifying them. The survey first presents the main challenges of adopting NVM in any level of memory hierarchy and proceeds to discuss the many approaches present in the literature detailing the most relevant ones.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In [100], the authors introduce architectural designs of PCM techniques to address the problems of limited write endurance, potential long latency, high energy writes, power dissipation, and some concerns for memory privacy. In [101], the authors present a comprehensive survey and review of PCM device related computer architectures and software. Some other interesting surveys such as [102] focuses on architecturally integrating four NVM technologies (PCM, MRAM, FeRAM, and ReRAM) into the existing storage hierarchy, or focuses on the software optimizations [103] of using NVMMs for storage and main memory systems.…”
Section: Contributionsmentioning
confidence: 99%
“…Our survey is different from those surveys in three-folds. First, the articles [100,101] both put a focus on the PCM system designs from the perspective of computer architecture. In contrast, our paper mainly focuses on system works of using hybrid memories from the dimensions of memory hierarchy, system software, and applications.…”
Section: Contributionsmentioning
confidence: 99%